The Ferry Transport Passenger Service Standard On The Ferry Port Of Kolaka, Southeast Celebes Province - Hendri Ginting; Elfita Agustini; Esa Sakti Al Qadri Amanu (IWTJ : International Water Transport Journal, 2019)
The Ferry Port of Kolaka in Southeast Celebes provincial is a port that serves Kolaka main path - Bajoe. The existence of this track becomes very important in the effort to support economic develoRegulationent in the region Kolaka. The level of service perceived by the service user is affecting the implementation of the transport activities of service perceived Ferries especially at ports must meet the standards of passenger service because they are consumers who determine whether or not a developed transportation system. The method used to analyze the existing problems is the evaluation of the suitability of the level of minimum service standards with existing conditions. Based on the calculation of the level of conformity was no difference between the suit that is not accordance with of every aspect has been assessed. As for the aspects of service that accordance with in Kolaka ferry port whereas only 9 aspect that does not fit as many as 23 aspects with a weighted sum of 32 ratings. Based on this analysis it was concluded that there is less service than some ferry transport as the temperature control rooms, information services, manual evacuation routes, power source, special disable passengers, stretchers, FIRST AID, absence of fire extinguishers and unavailability of transport information continued to not meet the requirements of Standard Passenger Service at the Port